2017
DOI: 10.1016/j.bbrc.2016.12.077
|View full text |Cite
|
Sign up to set email alerts
|

Cultured human amniocytes express hTERT, which is distributed between nucleus and cytoplasm and is secreted in extracellular vesicles

Abstract: Our study demonstrates for the first time the expression of the full protein hTERT by AFCs and its release outside the cell mediated by EVs, indicating a new extra telomeric role for this protein. This finding represents an initial but crucial evidence for considering AFCs derived EVs as new potential sources for tissue regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…The purity, size distribution and number of separated EVs were revealed by Atomic Force Microscopy (AFM) and Colloidal nanoplasmonic (CONAN) assay ( Fig 2F, 2G and 2H). Western blot analysis, using antibodies against surface and internal makers, excluded contamination by other membrane fragments (GM-130), confirmed EV-specific marker-expression (Annexin XI, Annexin V and TSG-101), TERT-expression (in accordance with a recently-discovered biomarker on amniocyte-derived EVs [24]) and characteristic CD29 protein-expression of the parental MSCs (Fig 2I).…”
Section: Resultssupporting
confidence: 66%
“…The purity, size distribution and number of separated EVs were revealed by Atomic Force Microscopy (AFM) and Colloidal nanoplasmonic (CONAN) assay ( Fig 2F, 2G and 2H). Western blot analysis, using antibodies against surface and internal makers, excluded contamination by other membrane fragments (GM-130), confirmed EV-specific marker-expression (Annexin XI, Annexin V and TSG-101), TERT-expression (in accordance with a recently-discovered biomarker on amniocyte-derived EVs [24]) and characteristic CD29 protein-expression of the parental MSCs (Fig 2I).…”
Section: Resultssupporting
confidence: 66%
“…This increase could have significant functions in the viral life cycle of HPV, therefore playing an essential role in cell immortalization and in the process of malignant transformation (2,22). Regarding the cellular localization of the hTERT protein, the reported findings in different tissues are few (14,15,(22)(23)(24)(25)(26)(27)(28)(29). In some reports, it has been shown that although hTERT is expressed in the nucleus of benign tissues, it is gradually transferred to the cytoplasm in the process of malignant transformation (2,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…To obtain conditioned media for exosome isolation, HaCaT cells were grown in complete DMEM until the reach of 70% confluence, and then the media were removed and renewed with DMEM without FBS for 48 hours. Afterward, conditioned media were collected and processed with a serial centrifugation protocol (37,38). Briefly, conditioned media were centrifuged firstly at 800 g for 30 minutes to pellet and discard possibly contained apoptotic bodies and cellular debris.…”
Section: Methodsmentioning
confidence: 99%